2011
DOI: 10.1371/journal.pntd.0001048
|View full text |Cite
|
Sign up to set email alerts
|

Ziehl-Neelsen Staining Technique Can Diagnose Paragonimiasis

Abstract: BackgroundWe evaluated the Ziehl-Neelsen staining (ZNS) technique for the diagnosis of paragonimiasis in Laos and compared different modifications of the ZNS techniques.MethodologyWe applied the following approach: We (1) examined a paragonimiasis index case's sputum with wet film direct examination (WF) and ZNS; (2) re-examined stored ZNS slides from two provinces; (3) compared prospectively WF, ZNS, and formalin-ether concentration technique (FECT) for sputum examination of patients with chronic cough; and (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 18 publications
0
18
0
1
Order By: Relevance
“…In sputum samples, the fresh eggs can be detected with Ziehl-Neelsen staining, which appears to be superior to wet mount. 7 In tissue specimens (after formalin fixation), the eggs have a characteristic yellow-brown, refractile wall. Serologic tests, including complement fixation, countercurrent immunoelectrophoresis, and enzyme-linked immunosorbent assay, are available for identification of P. westermani, and are more useful for extrapulmonary disease when eggs may not be shed in the sputum.…”
Section: Discussionmentioning
confidence: 99%
“…In sputum samples, the fresh eggs can be detected with Ziehl-Neelsen staining, which appears to be superior to wet mount. 7 In tissue specimens (after formalin fixation), the eggs have a characteristic yellow-brown, refractile wall. Serologic tests, including complement fixation, countercurrent immunoelectrophoresis, and enzyme-linked immunosorbent assay, are available for identification of P. westermani, and are more useful for extrapulmonary disease when eggs may not be shed in the sputum.…”
Section: Discussionmentioning
confidence: 99%
“…The Ziehl-Neelsen staining (ZNS) technique, used to stain mycobacteria in sputum, had long been assumed to destroy lung fl uke eggs [ 247 ]. Thus, diagnosticians trying to exclude infections with either of these pathogens have tested sputum samples separately for each.…”
Section: Parasitological Diagnosismentioning
confidence: 99%
“…A recent reevaluation of the ZNS technique, and especially of modifi cations that avoid long periods of heating the slide, has shown that destruction of eggs can be avoided. The ZNS technique therefore provides a low-cost method for distinguishing between paragonimiasis and tuberculosis [ 247 ]. Furthermore, the method reduces the risk of tuberculosis transmission [ 247 ] and the ZNS slides can be kept for further evaluation and archiving.…”
Section: Parasitological Diagnosismentioning
confidence: 99%
“…Paragonimiasis might be affected by eosinophilia or the presence of microcysts seen in lung radiographs. Moreover, in cases of dual infection, paragonimiasis may lead to misinterpretation of TB treatment failure when lung symptoms persist 2. As in Thailand, despite anecdotic reports among migrants, the diagnosis of paragonimiasis was not accurate in Laos during the 1980s–2000s 5,6…”
mentioning
confidence: 99%
“…Recently, we also questioned an old paradigm of medical parasitology 2. Ziehl-Neelsen staining, as conducted 50 years ago, was known to deteriorate Paragonimus eggs.…”
mentioning
confidence: 99%